Model Pembelajaran Fikih Praktis sebagai Sarana Internalisasi Nilai Religiusitas dalam Pengurusan Janazah - Syifa Ullinnas; Hamzah Irfanda (Educational Research Indonesia, 2025)
Effective fiqh instruction requires an approach that goes beyond cognitive understanding by integrating affective and psychomotor dimensions to achieve deep internalization of religious values. This study examines a practical fiqh learning model within the context of Islamic funeral rites as a medium for strengthening students’ religious internalization. Using a qualitative literature-based approach, the analysis explores how practical fiqh instruction can systematically integrate theory and hands-on practice to enhance both conceptual comprehension and relevant skills. The findings indicate that a practical learning model grounded in constructivism, observational learning, and Kolb’s experiential learning cycle effectively incorporates Glock and Stark’s five dimensions of religiosity through three stages of value internalization: transformation, transaction, and transinternalization. Learning strategies such as demonstration, direct practice, simulation, critical reflection, and field visits are shown to foster awareness of mortality, social solidarity, empathy, and modesty. Despite challenges—including limited facilities, emotional resistance, and varying teacher competencies—the model offers significant contributions to Islamic education by promoting a more relevant, meaningful, and applicable learning experience